Can information be too much? the moderating role of Covid-19 information on the effect of job stress on job performance - Adra Rida Mahila; Rosaly Franksiska (Diponegoro International Journal of Business, 2021)
During the Covid-19 pandemic, many governments require companies to promote a work from home policy. However, many occupations cannot be done at home, putting the employees at increased health risk and increasing job stress. The purpose of this study is to examine whether job stress negatively affects job performance. Furthermore, we also examine the moderating effect of Covid-19 information on the relationship between job stress and job performance. Our respondents are employees who work in manufacturing firms in Salatiga and still have to work from the office during the pandemic. The data were collected using an online questionnaire, and the total number of respondents is 105. Our analysis using moderated regression analysis founds that job stress negatively influences job performance. We also found that Covid-19 information moderates the relationship between job stress and job performance.